Arctic soil development on a series of marine terraces on central Spitsbergen, Svalbard: a combined geochronology, fieldwork and modelling approach - W. M. van der Meij; A. J. A. M. Temme; C. M. F. J. J. de Kleijn; T. Reimann; G. B. M. Heuvelink; Z. Zwoliński; G. Rachlewicz; K. Rymer; M. Sommer (SOIL, 2016)
Soils in Arctic regions currently enjoy attention because of their sensitivity to climate change. It is therefore important to understand the natural processes and rates of development of these soils. Specifically, there is a need to quantify the rates and interactions between various landscape- and soil-forming processes. Soil chronosequences are ideal natural experiments for this purpose. In this contribution, we combine field observations, luminescence dating and soil–landscape modelling to improve and test our understanding of Arctic soil formation. The field site is a Holocene chronosequence of gravelly raised marine terraces in central Spitsbergen. Field observations show that soil–landscape development is mainly driven by weathering, silt translocation, aeolian deposition and rill erosion. Spatial soil variation is mainly caused by soil age, morphological position within a terrace and depth under the surface. Luminescence dating confirmed existing radiocarbon dating of the terraces, which are between  ∼  1.5 and ∼  13.3 ka old. The soil–landscape evolution model LORICA was used to test our hypothesis that the field-observed processes indeed dominate soil–landscape development. Model results additionally indicated the importance of aeolian deposition as a source of fine material in the subsoil for both sheltered and vegetated trough positions and barren ridge positions. Simulated overland erosion was negligible. Consequently, an un-simulated process must be responsible for creating the observed erosion rills. Dissolution and physical weathering both play a major role. However, using present-day soil observations, the relative contribution of physical and chemical weathering could not be disentangled. Discrepancies between field and model results indicate that soil formation is non-linear and driven by spatially and temporally varying boundary conditions which were not included in the model. To conclude, Arctic soil and landscape development appears to be more complex and less straightforward than could be reasoned from field observations.